Pelatihan Penyusunan dan Pengevaluasian Program Bimbingan dan Konseling Komprehensif pada MGBK SMA dan SMK di Kabupaten Tanggamus - Mujiyati; Syarifuddin Dahlan; Redi Eka Andriyanto; Sofwan Adiputra (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2023)
This community service activity aims to provide guidance and counseling teacher understanding and knowledge and skills in preparing and evaluating comprehensive guidance and counseling programs in schools. The methods used to achieve these objectives, namely: (1) presentation of the material; presents an analysis of various programming concepts and how to evaluate them; (2) brainstorming; dig up information related to participants' understanding and efforts that have been made and (3) practice; improve the ability of participants in preparing and evaluating programs. The training activities were carried out for 2 days at SMKN 1 Kota Agung Barat with 40 guidance and counseling teachers participating in the Guidance and Counseling Teacher Consultation (MGBK) for SMA and SMK in Tanggamus Regency. The results of this community service activity show that the level of understanding of the guidance and counseling teachers on the concepts and praxis of the guidance and counseling assessment has increased with an average capacity improvement score of 24.11% from before the training was carried out. The percentage increase shows that the training is beneficial to participants in preparing and evaluating programs.